Enhanced solubilization of insoluble silicate from quartz and zeolite minerals by selected Aspergillus and Trichoderma species - Laksmita Prima SANTI (E-Journal Menara Perkebunan, 2020)
Silicon (Si) is a major component of sand, silt and clay particles of soils. Available silica as silicic acid (H4SiO4) present in soil solution is considerably low, only in the range of 3.5–40.0 mg Si L-1. To improve plant-available Si in the soil, silicate-solubilizing fungi (SSF) are potentially important in solubilizing insoluble forms of silicate (SiO2). The objectives of this study were to determine silicate solubilizing capacity and organic acid produced by seven SSF isolates on Bunt and Rovira media by using 0.25% (w/v) magnesium trisilicate (Mg2O8Si3), quartz, and zeolite as a silica source. Determination of SSF isolates potential in Si solubilization was carried out in a completely randomized design with three silica sources and three replicates. The results indicated that all SSF were capable of producing acetic, citrate, and oxalic acids and enhancing the solubilization of insoluble silicates. Trichoderma polysporum and Aspergillus niger BCCF194 were the best isolates of SSF. Furthermore, there was significantly (p<0.05) positive correlation between solubilizing silicate capacity by using quartz or zeolite as a silica source on Bunt and Rovira media with incubation time (R2 = 0.79-0.99) and citric acid production (R2= 0.97-0.99) from T. polysporum and A. niger BCCF194